Histological, microecological and transcriptomic physiological responses underlying hypoxia and reoxygenation adaptation in yellowtail kingfish (Seriola lalandi) - Zhou, Heting; Jiang, Yan; Xu, Yongjiang; Cui, Aijun; Feng, Yuan; Jin, Zhixin; Wang, Bin (Frontiers in Marine Science, 2023)
Yellowtail kingfish has emerged as one of the most promising marine fishes for aquaculture in China because it is tasty, fast growing, and has high economic value. Hypoxia is a frequently encountered phenomenon during fish culture, which can cause serious physiological stress and even death of farmed fish. To investigate the tolerance and adaptability to hypoxia of farmed yellowtail kingfish, juveniles were exposed to hypoxia for 5 days and then returned to normoxia for another 5 days. The results showed that hypoxia increased the gill lamellae length and spacing, which were reversible post-reoxygenation. At the genus level, the relative abundances of Prevotella, Bacteroides, Roseburia, and Blautia in the gastrointestinal tract increased under hypoxia and were maintained post-reoxygenation. The liver transcriptome revealed that, compared with normoxia group, the different expression genes (DEGs) were mainly enriched in Steroid biosynthesis and PPAR signaling pathways in hypoxia group. Compared with normoxia group, the DEGs were mainly enriched in Ribosome biogenesis in eukaryotes, Steroid biosynthesis, Fatty acid biosynthesis, and PPAR signaling pathways in reoxygenation group. Furthermore, compared with hypoxia group, the DEGs were mainly enriched in Ribosome biogenesis in eukaryotes and Ribosome pathways in reoxygenation group. In contrast to normoxia, of the key genes of the PPAR signaling pathway, FABP4 was significantly downregulated, and SCD-1 and FATP were significantly upregulated. These findings indicated reduced lipid deposition and increased lipid decomposition in liver under hypoxia. The genes including PPARα, SCD-1, ANGPTL4, and FASN were significantly upregulated in lipid metabolism-related pathways, which indicated that lipid metabolism activity was more vigorous during reoxygenation. In contrast to the hypoxia group, almost all of the genes involved in Ribosome biogenesis in eukaryotes and Ribosome pathways for protein processing were significantly upregulated during reoxygenation; this is probably related to the clearance of misfolded proteins and the folding of the new proteins repairing there is damage to the body. The present results shed light on the possible synergetic function of lipid metabolism, protein repairment and synthesis, and gastrointestinal microbiota in resistance and homeostasis maintenance of yellowtail kingfish coping with hypoxic stress in aquaculture.